Cloning and characterization of bovine growth hormone (bGH) gene from Malaysian gaur (Bos gaurus hubbacla) - Muhammad Hafiznur, Yunus (Universiti Sains Malaysia, 2008)
Total genomic DNA from Malaysian gaur (Bos gaurus hubbacla) was isolated from whole blood. The genomic DNA was then subjected to PCR amplification using specific primers for bovine growth hormone gene (bGH). This PCR product which represents part of the bGH gene was cloned into pCR® 2.1 TOPO® cloning vector before sent for sequencing analysis. The nucleotide sequence of the gene coding regions was found to be identical with that of GenBank database sequence of Bos gaurus growth hormone mRNA sequence except for two nucleotides position (position 101 and 128). The current database of Bos gaurus growth hormone mRNA sequence at GenBank showed one unknown nucleotide at position 128 which denoted as N in the sequence. The finding of this study determined that the nucleotide base at position 128 is cytosine (C). The entire cloned gene sequence is 665 bp in length and contains 333 bp coding regions that code for 110 amino acid residue. The in-silico restriction mapping site analysis carried out in this study revealed that 70 enzymes produce unique site when they cut the sequence. A comparison of the cloned Malaysian gaur bGH gene with Bos taurus (local cattle) growth hormone mRNA sequence also showed a high homology between both sequences.